HOW MUCH DOES AN AFFORDABLE HOUSE COST TO BE PAID BY YOUNG PROFESSIONALS IN GREATER KL, MALAYSIA? - Sohaimi, Nor Suzylah (PLANNING MALAYSIA, 2022)
Affordability of housing has been a hot topic among various socioeconomic groups. Surprisingly, given the current situation, the majority of the young generation is negatively affected by this stressful issue. This study, therefore, focuses on young professional groups from the built environment profession, namely, the engineer, architect, urban planner, and quantity surveyor. These professional groups also earn an income between B40, M40 and T20. Two research objectives were composed in this study: (1) To measure the monthly affordable housing cost and (2) To define affordable housing types by different household income groups amongst young professional based on the residual income model (RIM), which is used to measure housing affordability. The surveys were distributed amongst 341 respondents selected through stratified random sampling. The findings have revealed that B40 can only bear a monthly housing’ costs not exceeding MYR 728, followed by M40 and T20 around MYR 2503 and MYR 6159, respectively. Hence, the B40 group had lesser house option types, i.e., around ten house types compared to M40 and T20.